Os especialistas em educação para a América Latina (1958-1966) - Maluhy, Cláudia Vercesi (2010)
The Main Unesco Project Number 1, presented in May 1956 during the Latin-American Regional Conference on Charge-Free and Mandatory Elementary Education, had as central aims: the broadening of elementary school, the eradication of illiteracy and teachers training. Interested in assisting the Project implementation, between 1958 and 1966, the Centro Regional de Pesquisas Educacionais de São Paulo (CRPE/SP), in agreement with the United Nations, Educational, Scientific, and Cultural Organization (Unesco), the Instituto Nacional de Estudos Pedagógicos (Inep), and the Universidade de São Paulo (USP), organized the Cursos de Especialistas em Educação para a América Latina (CEEAL), focused on the university education for educators (administrators, supervisors, specialists in curricula, advisors, principals, etc.) from 19 Latin-American countries. To understand CEEAL aims and organization, which is the main object of the present work, we have described and analyzed Unesco documents, CRPE/SP publications, monographs written by the participants, and theoretical production of educators and socialists somehow involved with the issue. From all those presented documents, we have tried to reconstruct the historical process that originated those courses, answering the questions related to the political and economical role given to the primary school during the 1950 s, as well as their relationship with ―developmental‖ ideologies and the defense of the democratization of education